PENGARUH SCHOOL WELL-BEING TERHADAP HASIL BELAJAR SISWA DI SMK NEGERI 1 TONDANO - Tengker, Melita; Tuerah, Philoteus E. A.; Tilaar, Anetha L. F. (Dharmas Education Journal (DE_Journal), 2024)
Various challenges and major changes are being faced by the vocational school level education system in Indonesia. The demands of the world of work and industry are not fully met by the vocational school curriculum in Indonesia. The number of unemployed among vocational school graduates has become quite large as a result. is School Well-Being Whether or not it influences student learning outcomes at SMK Negeri 1 Tondano is the aim of this research. The survey method was used in this quantitative research. Questionnaires and document review were used in data collection. A total of 78 students were sampled in this research. Correlation Product Moment and regression analysis is applied in data analysis techniques. It is known from the results of the analysis product moment that the value of rcount greater than rtable namely 0.900 > 0.2227. It is known that the direction of a positive relationship is indicated by a correlation coefficient of 0.900. The regression equation model is obtained from the results of regression analysis, namely. So students with school well-being good also has good learning outcomes which is also shown by a regression coefficient of 0.850, a significance value of 0.000 < 0.05, and a t valuecount amounting to 17,952 > ttable amounting to 1,668. This research concludes that School Well-Being has a positive and significant influence on the learning outcomes of class X students at SMK Negeri 1 Tondano.